MEDIASI PERSPEKTIF HUKUM ISLAM (STUDI PERMA NO. 1 TAHUN 2008 TENTANG PROSEDUR MEDIASI DI PENGADILAN) - Bashori, Imam Ali (ISTINBATH JURNAL HUKUM, 2015)
AbstractMediation is an alternative way to resolve disputes. With the approach of a win-win solution, mediation can bring a sense of fairness in resolving disputes without going through trial procedures are familiar with legal terminology that is difficult to understand by the general public. However, not all disputes can be resolved through mediation way. Perma No. 1 of 2008 on mediation procedure in court mediation limit applies only to disputes / civil cases. This paper questions the back of the scope and types of cases that can use alternative settlement by way of mediation. Here will be presented mediation according to the viewpoint of Islam well as analysis for Perma No. 1 Year 2008. Islamic law is an integral part of building laws in Indonesia, so that it opens the possibility of treasures in Islamic law becomes the input for the law in Indonesia, including on mediation. In the mediation of Islam known as Sulh encompass a broader scope than the scope of mediation in Perma No. 1 Year 2008. This paper will parse the opportunity to broaden the scope of mediation in Perma No. 1 of 2008 is based on the viewpoint of Islamic law, one of which is mediation in criminal cases. The State does not only present as a punisher, but more widely present state as a mediator in criminal matters (public). Keywords: Court, mediation, peace, dispute, Perma No. 1 Year 200 AbstrakMediasi merupakan salah satu alternative cara dalam menyelesaikan sengketa. Dengan pendekatan win-win solution, mediasi bisa menghadirkan rasa keadilan dalam menyelesaikan persengketaan tanpa melalui prosedur persidangan yang akrab dengan istilah-istilah hukum yang sulit dimengerti oleh masyarakat awam. Namun tidak semua sengketa bisa diselesaikan melalui jalan mediasi. Perma No. 1 Tahun 2008 tentang prosedur mediasi di Pengadilan membatasi mediasi berlaku hanya pada sengketa/perkara perdata. Tulisan ini menyoal kembali tentang ruang lingkup dan jenis perkara yang bisa menggunakan alternative penyelesaian dengan jalan mediasi. Di sini akan dipaparkan mediasi menurut sudut pandang islam sekaligus menjadi analisis bagi Perma No. 1 Tahun 2008. Hukum Islam merupakan bagian tidak terpisahkan dari bangunan hukum di Indonesia, sehingga terbuka kemungkinan khazanah dalam hukum islam menjadi masukan bagi hukum di Indonesia termasuk tentang mediasi. Dalam Islam mediasi yang dikenal dengan istilah Sulh mencakup ruang lingkup yang lebih luas dibanding dengan ruang lingkup mediasi pada Perma No. 1 Tahun 2008. Tulisan ini akan mengurai peluang untuk memperluas ruang lingkup mediasi pada Perma No. 1 Tahun 2008 berdasarkan sudut pandang Hukum Islam, salah satunya adalah mediasi pada perkara pidana. Negara tidak hanya hadir sebagai penghukum, namun lebih luas Negara hadir sebagai mediator pada perkara pidana (public). Kata kunci: Pengadilan, mediasi, perdamaian, sengketa, Perma No. 1 Tahun 2008